Always together or alone first? Effects of type of collaborative translation on Spanish L2 development. (3rd July 2017) - Cerezo, Luis
ABSTRACT: Rooted in socio-constructivism, the present article investigates the effects of type of collaborative translation on Spanish L2 development, triangulating data from task performance, learning outcomes, and learners' perceptions. Thirteen dyads of college students participated in a within-subjects repeated-measures experimental study, translating authentic texts in two ways: collaborating from the get-go and after working alone first. Results showed that while participants translated more lexical items accurately when working together from the get-go, both types of collaborative translation propelled similar learning gains in lexis and grammar. Of the two, only lexical learning was retained after one week. Participants, contrary to results, reported a clear preference for working alone first, which they perceived as more conducive to learning.